Development of a patient decision aid for the initiation of urate-lowering therapy in gout patients. Issue 1 (19th February 2022) - te Kampe, Ritch; Boonen, Annelies; Jansen, Tim; Janssen, Matthijs; de Vries, Hein; van Durme, Caroline
Abstract : Aim: Shared decision-making improves patients' experiences with care, satisfaction with management decisions and possibly health outcomes. This study describes the development of a decision aid (DA) that supports patients with gout and their physicians in a face-to-face clinical setting to (a) decide whether or not to (re)start urate-lowering therapy (ULT) and (b) agree on the preferred ULT. Methods: Recommendations of the International Patient Decision Aid Standards group guided the development. A steering group of experts in gout and health services research specified the scope. Nominal group technique meetings were organised in which patients ranked the importance of preidentified potential characteristics/attributes of ULT and discussed further needs regarding the DA. A literature search was conducted to collect evidence on gout outcomes with and without ULT. Subsequently, the DA prototype was designed and adjusted using feedback from the steering group and results of cognitive debriefing interviews among five gout patients. Results: The final DA consists of six pages. First, the DA clarifies the decision at stake and describes gout including its risk factors, the role of lifestyle and treatment of flares. Next, risk of future flares with and without ULT in relation to serum uric acid levels is described and visualised. Relevant attributes of ULT are presented in an option grid distinguishing first-line and second-line ULT. Finally, patients' believes and preferences are explicitly addressed before making the shared decision. Conclusion: This study provides initial support for usability of a DA for gout patients eligible for starting ULT.